Lighting system automation using a relay based on radio frequency identification tag input and kiosks’ information access with Telegram application in the modern market - Ngalimin, Libratyan Jhon; Christina, Erma Triawati; Kristyawati, Desy (Applied Research and Smart Technology (ARSTech), 2023)
Advancements in technology necessitate the swift and efficient management of systems, particularly concerning electricity consumption and information dissemination. To address this, a prototype was developed to automate lighting systems and display kiosk information in modern markets. Key components utilized include an RFID reader, GPS module, NodeMCU ESP8266, and relays, all of which played crucial roles in the functioning of the prototype. The primary objective was to create a device capable of automatically controlling the lighting system through relays, triggered by RFID inputs, while also relaying kiosk information via the Telegram application. For instance, when a registered RFID tag is tapped while the shop is open and the lamp is initially on, the lamp will be switched off, ensuring energy efficiency and timely response. The GPS module is employed to obtain location data, which, along with kiosk open/close status, can be conveniently accessed through the Telegram app. This integration of the GPS module enhances the prototype's functionality by providing valuable location-based information, making it easier for users to monitor and access the information remotely. Test results demonstrate that the RFID tag can be read from a maximum distance of 4.5 cm, with an average processing time of 2.47 seconds for lamp switching and 5.6 seconds for accessing information. These performance metrics validate the efficacy of the prototype methodology in achieving its intended goals of automation, energy efficiency, and seamless information dissemination in modern markets.